The Factors Associated with Utilization of Sexual and Reproductive Health Services Among Batwa Adolescents in Kisoro District Uganda: A Cross-Sectional Study. - Kyambade, Robert; Nwankwo, Chinenye Mercy; Tamu, Munezero J.B.; Okafor, Christiana (Kabale University, 2024)
BACKGROUND: Adolescents’ sexual and reproductive health (SRH) needs are crucial and meeting such needs presents with a unique challenge among minority and marginalized populations, such as the Batwa of southwestern Uganda. OBJECTIVE: The study investigated the factors influencing utilization SRH among Batwa minority adolescents in Kisoro district. METHODS: A cross-sectional study was adopted, incorporating both qualitative and quantitative methods. Data was collected from a random sample of 241 adolescents from a target population of 608 aged 10–18 years using validated interviewer-administered questionnaires, focus group discussions, and key Informants interviews. Qualitative data were coded into themes and analyzed thematically, while quantitative data was analyzed using frequencies, Chi-square tests, and multinomial logistic regression. RESULTS: The majority of adolescents (59.3%, CI: 52.84 - 65.60), were aware of the voluntary counseling services provided, 76.8% (CI: 70.91 - 81.94) were aware of family planning services, but 53.5% (CI: 47.01 - 59.95) were not aware of SHR related issues. About 44.8% (CI: 38.24 - 51.36) had visited health facility once in the past year, while 55.2% (CI: 48.67 - 61.57) had never utilized adolescent SRH. Furthermore, 71.8% (CI: 65.43 - 77.47) were aware of adolescent-friendly SRH services. Factors associated with SRH service utilization included education (p = 0.029), source of medical services (p< 0.001), and proximity to health facilities (p < 0.001). Findings from the multinomial logistic regression showed that SRH services utilization was associated with an increased odd of distance to health facilities (OR 3.74, 95% CI: 1.86 - 7.53). CONCLUSION: The study highlights high levels of SRH services awareness but low levels of utilization among Batwa adolescents. Strategic planning of reproductive health service programs in Batwa communities is strongly recommended to enhance accessibility, service ownership and utilization.